07 | Role of health education on human papillomavirus vaccination willingness among a sample of students in the Local Health Authorities of Agrigento, Palermo and Trapani, Sicily - F. Cacioppo; C. Amodeo; N. Bonaccorso; M. Sciortino; E. Zarcone; M. Tocco; L. Pipitone; A. Carubia; L. D'Azzo; T. Vitello; G. Bosco; S. Palmeri; et al. (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. HPV is one of the most common causes of sexually transmitted infections (STIs) worldwide. Strategies to counteract HPV-related infections and diseases include primary prevention measures, such as vaccination, and secondary prevention measures, such as Pap test and HPV DNA test. The objective of this study is to assess the extent to which health education and knowledge levels influence students’ propensity to make informed health choices, with particular reference to HPV vaccination. Materials and Methods. A total of 2,111 middle and high school students from the provinces of Agrigento (1 schools), Palermo (2 schools), and Trapani (26 schools) participated in the study. They were administered a questionnaire designed to assess their knowledge of STIs, particularly HPV, as well as their attitudes toward and adherence to HPV vaccination. Participation in the study was contingent upon the parents receiving the information sheet and signing the informed consent form. Results. The sample consisted of 780 (36.3%) males and 1,371 (63.7%) females. 64.6% of participants reported being vaccinated against HPV, 22.6% reported not being vaccinated, and 12.8% reported not knowing their vaccination status; vaccination coverage was similar among males (62.8%) and females (61.6%). The majority of students (79.4%) reported not having yet had sexual intercourse, while 11.8% reported using contraceptive methods. 89.4% of students reported having heard of HPV (86.8% of males and 90.8% of females). This awareness is associated with greater willingness to be vaccinated (8.8 vs. 7.3 among those who had never heard of it; p-value